Game Edukatif Membaca Al-Qur’an (Ilmu Tajwid) Berbasis Android - Muhammad Zainal Abidin; Tri Listyorini (SINTECH (Science and Information Technology) Journal, 2018)
Tajweed is one of the material in reading the Holy Qur'an. As well as learning Indonesian, learning to read the Holy Qur'an should know Tajweed. The development of children now, much to exclude learning due to many games on the phone. This becomes our chance to make educative games. Packaging games to read the Qur'an in this case Tajweed become more interactive since the children are not only play but also get the material. Using the prototype method, this educational game reading alquran is packed into a valuable educational game. The results of this study is educational games on how to read alquran (Tajweed) which can be used by all smartphone which uses android platform